Evolution of host specificity in monogeneans parasitizing African cichlid fish - Mendlová, Monika; Šimková, Andrea (Parasites & vectors, 2014)
BACKGROUND: The patterns and processes linked to the host specificity of parasites represent one of the central themes in the study of host-parasite interactions. We investigated the evolution and determinants of host specificity in gill monogeneans of Cichlidogyrus and Scutogyrus species parasitizing African freshwater fish of Cichlidae. METHODS: We analyzed (1) the link between host specificity and parasite phylogeny, (2) potential morphometric correlates of host specificity (i.e. parasite body size and the morphometrics of the attachment apparatus), and (3) potential determinants of host specificity following the hypothesis of ecological specialization and the hypothesis of specialization on predictable resources (i.e. host body size and longevity were considered as measures of host predictability), and (4) the role of brooding behavior of cichlids in Cichlidogyrus and Scutogyrus diversification. RESULTS: No significant relationships were found between host specificity and phylogeny of Cichlidogyrus and Scutogyrus species. The mapping of host specificity onto the parasite phylogenetic tree revealed that an intermediate specialist parasitizing congeneric cichlid hosts represents the ancestral state for the Cichlidogyrus/Scutogyrus group. Only a weak relationship was found between the morphometry of the parasites' attachment apparatus and host specificity. Our study did not support the specialization on predictable resources or ecological specialization hypotheses. Nevertheless, host specificity was significantly related to fish phylogeny and form of parental care. CONCLUSIONS: Our results confirm that host specificity is not a derived condition for Cichlidogyrus/Scutogyrus parasites and may reflect other than historical constraints. Attachment apparatus morphometry reflects only partially (if at all) parasite adaptation to the host species, probably because of the morphological similarity of rapidly evolved cichlids (analyzed in our study). However, we showed that parental care behavior of cichlids may play an important role linked to host specificity of Cichlidogyrus/Scutogyrus parasites.
Keywords: Host Specificity; fylogeneze; Animals; Biological Evolution; Cichlids; infekce červy třídy Trematoda; hostitelská specificita; cichlidy; ploštěnci; biologická evoluce; interakce hostitele a parazita; Host-Parasite Interactions; Phylogeny; Platyhelminths; zvířata; nemoci ryb; Trematode Infections; Fish Diseases